2019
DOI: 10.1111/1759-7714.13092
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of postoperative complications between different operation methods for esophageal cancer

Abstract: Background We explored the selection of surgical method and differences in postoperative complications in patients with esophageal cancer (EC). Methods The data of 434 patients with EC who underwent thoracic surgery at the Jiangsu Provincial People's Hospital between January 2011 and December 2016 were collected. Patients were divided into three groups: Sweet surgery (143 cases), Ivor–Lewis surgery (232 cases), and minimally invasive esophagectomy (MIE, 59 cases). The number of postoperative days, number of ly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…A study including 434 ESCC patients who underwent radical resection revealed that complication had no effect on long-term survival, despite an increasing immediate postoperative outcome and hospital mortality. 46 Another research including 1100 EC patients with resection indicated that AL did not adversely affect survival (the incidences of AL was 9.6%). 47 While another study indicated an opposite result.…”
Section: Discussionmentioning
confidence: 99%
“…A study including 434 ESCC patients who underwent radical resection revealed that complication had no effect on long-term survival, despite an increasing immediate postoperative outcome and hospital mortality. 46 Another research including 1100 EC patients with resection indicated that AL did not adversely affect survival (the incidences of AL was 9.6%). 47 While another study indicated an opposite result.…”
Section: Discussionmentioning
confidence: 99%
“…The radical resection of esophageal cancer is primarily categorized into three surgical methods based on the tumor’s location: Ivor Lewis (via right thoracic and abdominal approach), McKeown (via the abdomen and left neck approach), and Sweet (via left thoracic approach). Ding et al have suggested that the incidence of PPCs is similar among those three methods ( 17 ). We did not choose to include only patients who underwent Ivor Lewis or McKeown surgery, but excluded the Sweet procedure from our study to mitigate potential interference caused by direct damage to the diaphragm associated with this method.…”
Section: Discussionmentioning
confidence: 99%
“… 20 Second, resection of the pulmonary vagal branch had little effect on lung function during the surgical procedure, particularly in patients with airway hyperresponsiveness, which may facilitate improvement and recovery of postoperative pulmonary function. 21 , 22 Third, the drug used for intraoperative anesthesia could have affected the pulmonary function. The anesthetic regimen of propofol + dexmedetomidine showed less damage than sevoflurane.…”
Section: Discussionmentioning
confidence: 99%